PERSIAPAN GURU KELAS 5 DALAM IMPLEMENTASI SISTEM PEMBELAJARAN MERDEKA BELAJAR DI SEKOLAH DASAR: Penelitian Deskriptif - Nur Darojati, Zulfa; Mulyani, Petra Kristi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aimed to determine the readiness of elementary school teachers in implementing the Kurikulum Merdeka, Indonesian curriculum. This type of research was qualitative descriptive research. The subject of this study is a 5th grade teacher at Elementary School. The instruments used interview and documentation. The data analysis in this study used qualitative data analysis, which summarized the results of the interview data that had been transcribed and coded. The results of this study showed that overall teachers were good at understand the mechanism of implementing the Kurikulum Merdeka, learning plan, and learning process. The readiness of the teaching modules according to the objectives and subjects is good. However, the aspect of providing teaching modules before carrying out learning is still lacking. Facilities and infrastructure to support learning are adequate. However, socialization from the government still needs to be increased. Teachers also try their best to prepare the Kurikulum Merdeka.